2005
DOI: 10.2139/ssrn.670231
|View full text |Cite
|
Sign up to set email alerts
|

Protection Motivation Theory and Contingent Valuation: Perceived Realism, Threat and WTP Estimates for Biodiversity Protection

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Clusters with a small number of members were avoided because of potential outliers. 31 For example, see Morey et al (2006), Scarpa and Menzel (2005) and Winter et al (2003). 32 For example, see Ben-Akiva et al (1999), andVredin Johansson et al (2006).…”
Section: Population Segmentationmentioning
confidence: 99%
“…Clusters with a small number of members were avoided because of potential outliers. 31 For example, see Morey et al (2006), Scarpa and Menzel (2005) and Winter et al (2003). 32 For example, see Ben-Akiva et al (1999), andVredin Johansson et al (2006).…”
Section: Population Segmentationmentioning
confidence: 99%
“…When attitudinal characteristics of respondents are incorporated into economic models as unobserved factors they are normally employed as explanatory variables [5,8,29] or as segmentation criteria for cluster analysis [30][31][32]. Some studies that have applied systematic measurement scales have shown mixed empirical findings for the attitude-WTP association [3,4,6,33].…”
Section: Introductionmentioning
confidence: 99%